2017
DOI: 10.1177/1687814017694831
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and experiment on tube hydroforming in a rectangular cross-sectional die

Abstract: Rectangular section parts created through hydroforming have good application prospects in the automotive industry because of their advantages of simple manufacturing procedure, high forming quality, and greater bending module than circular cross-sectional parts. Forming quality is directly influenced by the formed corner parameters of rectangular section parts. It is also a difficult matter in rectangular section hydroforming. The hydroforming rules of an aluminum alloy circular tube are regarded as the resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Modi and Kumar 5 studied the numerical simulation of AA 5182 aluminum alloy sheet, and the influence of hydroforming process parameters (such as pressure path, blank clamping force, and peak pressure) on the deep drawing formability of the square cup, and verified through experimental data. Moreover, Jia et al 6 examined experimental and numerical the influence of internal pressure, friction coefficient, and loading path on tube forming quality in the hydroforming process. They concluded that the wall thickness near the corner is influenced by different loading paths and the degree of thinning is small in the transition area.…”
Section: Introductionmentioning
confidence: 99%
“…Modi and Kumar 5 studied the numerical simulation of AA 5182 aluminum alloy sheet, and the influence of hydroforming process parameters (such as pressure path, blank clamping force, and peak pressure) on the deep drawing formability of the square cup, and verified through experimental data. Moreover, Jia et al 6 examined experimental and numerical the influence of internal pressure, friction coefficient, and loading path on tube forming quality in the hydroforming process. They concluded that the wall thickness near the corner is influenced by different loading paths and the degree of thinning is small in the transition area.…”
Section: Introductionmentioning
confidence: 99%
“…By loading paths, it is meant the internal pressure and the forced axial movement of the lower edge of the tube. The paths' choice and timings affect the final product's shape and mechanical characteristics [15][16][17]. If tube hydroforming is performed under proper loading conditions, a successful product result.…”
Section: Introductionmentioning
confidence: 99%
“…Forming quality is directly influenced by the formed corner parameters of rectangular section parts. It is also a difficult matter in rectangular section hydroforming [4]. Sample's roughness of the inner surface of tubes was measured and it was considered whether the sample properties are according to EN 10305-1.…”
Section: Introductionmentioning
confidence: 99%